'Dig where you stand': values-based co-creation through improvisation. Issue 3 (3rd July 2019) - García-Rosell, José-Carlos; Haanpää, Minni; Janhunen, Jenny
ABSTRACT: The concept of co-creation has been extensively discussed in tourism and hospitality research. Most studies focus mainly on exploring the involvement of customers in experience creation and the development of tourism services and innovations. Although this way of thinking can be valuable for creating competitive tourism services, it neglects other aspects of co-creation that may play an important role in tourism. Considering this gap, we work towards a more comprehensive understanding of value co-creation processes in small tourism firms by drawing upon cultural marketing and organisational improvisation. To illustrate this process, we present two company cases from northern Sweden, Treehotel and Icehotel. The empirical material used in this study consists of qualitative data collected via semi-structured interviews, participant and non-participant observation, and documentary materials. The study contributes to the co-creation discussion in tourism and hospitality by unpacking the role of human and non-human stakeholders, material resources, and unexpected events in the value co-creation processes within a small tourism firm context.